Taxonomic Novelty and Distinctive Genomic Features of Hot Spring Cyanobacteria - Alcorta, Jaime; Alarcón-Schumacher, Tomás; Salgado, Oscar; Díez, Beatriz (Frontiers in Genetics, 2020)
Several cyanobacterial species are dominant primary producers in hot spring microbial mats. To date, hot spring cyanobacterial taxonomy, as well as the evolution of their genomic adaptations to high temperatures, are poorly understood, with genomic information currently available for only a few dominant genera, including Fischerella and Synechococcus. To address this knowledge gap, the present study expands the genomic landscape of hot spring cyanobacteria and traces the phylum-wide genomic consequences of evolution in high temperature environments. From 21 globally distributed hot spring metagenomes, with temperatures between 32 and 75°C, 57 medium- and high-quality cyanobacterial metagenome-assembled genomes were recovered, representing taxonomic novelty for 1 order, 3 families, 15 genera and 36 species. Comparative genomics of 93 hot spring genomes (including the 57 metagenome-assembled genomes) and 66 non-thermal genomes, showed that the former have smaller genomes and a higher GC content, as well as shorter proteins that are more hydrophilic and basic, when compared to the non-thermal genomes. Additionally, the core accessory orthogroups from the hot spring genomes of some genera had a greater abundance of functional categories, such as inorganic ion metabolism, translation and post-translational modifications. Moreover, hot spring genomes showed increased abundances of inorganic ion transport and amino acid metabolism, as well as less replication and transcription functions in the protein coding sequences. Furthermore, they showed a higher dependence on the CRISPR-Cas defense system against exogenous nucleic acids, and a reduction in secondary metabolism biosynthetic gene clusters. This suggests differences in the cyanobacterial response to environment-specific microbial communities. This phylum-wide study provides new insights into cyanobacterial genomic adaptations to a specific niche where they are dominant, which could be essential to trace bacterial evolution pathways in a warmer world, such as the current global warming scenario.